Indoor nitrous acid and respiratory symptoms and lung function in adults. Issue 6 (27th May 2005) - Jarvis, D L; Leaderer, B P; Chinn, S; Burney, P G
Abstract : Background: Nitrogen dioxide (NO2 ) is an important pollutant of indoor and outdoor air, but epidemiological studies show inconsistent health effects. These inconsistencies may be due to failure to account for the health effects of nitrous acid (HONO) which is generated directly from gas combustion and indirectly from NO2 . Methods: Two hundred and seventy six adults provided information on respiratory symptoms and lung function and had home levels of NO2 and HONO measured as well as outdoor levels of NO2 . The association of indoor HONO levels with symptoms and lung function was examined. Results: The median indoor HONO level was 3.10 ppb (IQR 2.05–5.09), with higher levels in homes with gas hobs, gas ovens, and in those measured during the winter months. Non-significant increases in respiratory symptoms were observed in those living in homes with higher HONO levels. An increase of 1 ppb in indoor HONO was associated with a decrease in forced expiratory volume in 1 second (FEV1 ) percentage predicted (−0.96%; 95% CI −0.09 to −1.82) and a decrease in percentage FEV1 /forced vital capacity (FVC) (−0.45%; 95% CI −0.06 to −0.83) after adjustment for relevant confounders. Measures of indoor NO2 were correlated with HONO ( r  = 0.77), but no significant association of indoor NO2 with symptoms or lung function was observed. After adjustment for NO2 measures, the association of HONO with low lung function persisted. Conclusion: Indoor HONO levels are associated with decrements in lung function and possibly with more respiratory symptoms. Inconsistencies between studies examining health effects of NO2 and use of gas appliances may be related to failure to account for this association.